Razlaga preferenc do okolice in lokacije doma - Skifter Andersen, Hans (Urbani izziv, 2011)
This article is based on a survey carried out in Denmark that asked a random sample of the population about their preferences for home surroundings and locations. It shows that the characteristics of social surroundings are very important and can be divided into three independent dimensions: avoiding social nuisances, preferring social homogeneity and living close to one''s social network and place of origin. The study shows that most people have many detailed preferences, whereas some have very few. This confirms an earlier theory that some people are very connected to certain places with given characteristics and thus do not have priorities regarding home surroundings and locations. For others, mostly young people and singles, home is just a place to sleep and relax, whereas life is lived elsewhere. For this group, there are only preferences for location and there are few specific preferences for surroundings.
Keywords: Danska; Denmark; kriteriji; lokacija; stanovanja; stanovanjska naselja